2016
DOI: 10.1055/s-0036-1587692
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Direct Lateral Transpsoas Approach for the Resection of a Lumbar Plexus Schwannoma: Technique Report

Abstract: Objective Traditional techniques for resection of lumbar plexus tumors have been associated with approach-related morbidity. We describe a case utilizing a minimally invasive transpsoas lateral access approach to resect a retroperitoneal tumor of the lumbar plexus. Methods We report a case with an extradural retroperitoneal schwannoma of the L4 nerve root that was treated with a minimally invasive direct lateral transpsoas approach using atraumatic tissue dilators and an expandable tubular retracto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In our practice, periodic imaging is performed to monitor changes. In recent years, endoscopic or robotic minimally invasive surgery is also being employed for the management of retroperitoneal schwannomas, with an acceptable rate of surgical complications [1719]. Ji et al reported complication rates of 12.5% with laparoscopic resection of retroperitoneal schwannomas [18], while Liu et al reported complication rates of 12% with robotic resections of benign retroperitoneal tumors, including schwannomas [19].…”
Section: Discussionmentioning
confidence: 99%
“…In our practice, periodic imaging is performed to monitor changes. In recent years, endoscopic or robotic minimally invasive surgery is also being employed for the management of retroperitoneal schwannomas, with an acceptable rate of surgical complications [1719]. Ji et al reported complication rates of 12.5% with laparoscopic resection of retroperitoneal schwannomas [18], while Liu et al reported complication rates of 12% with robotic resections of benign retroperitoneal tumors, including schwannomas [19].…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, there are only a handful of case reports utilizing this technique for the resection of lumbosacral paravertebral and nerve sheath tumors and these have all been at lower lumbar levels (L3–L5). 3 4 5 6 To the best of our knowledge, this is the first reported case describing a nuanced technique performed at the thoracolumbar junction at L1. The unique anatomic considerations at this junctional level include adjacent proximity of diaphragm and 12th rib superiorly, lung pleura anteriorly, and retroperitoneum posteriorly.…”
Section: Discussionmentioning
confidence: 82%
“…Direct lateral approaches have risen in popularity for management of degenerative spine disease because the trajectory circumvents excess tissue in the posterior spine and allow for direct trajectory to the lateral spine. 30 Benjamin et al 9 reported resection of a small L4 lumbar plexus schwannoma using a direct lateral transpsoas approach using tubular retractors. One potential disadvantage of the direct lateral approach is that the location of the proximal nerve root is at the opposite end of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…One potential disadvantage of the direct lateral approach is that the location of the proximal nerve root is at the opposite end of the tumor. Benjamin et al 9 described docking their tubular retractor at the L4/5 disk space just anterior to the nerve root to allow for early identification of the nerve root. This patient developed new dysesthesias in the L4 distribution postoperatively and was discharged on day 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation